VARIATION IN CARBONATE CEMENT BY CATHODOLUMINESCENCE MICROSCOPIC ANALYSIS: IMPLICATION ON ENGINEERING PROPERTIES OF OOLITIC LIMESTONE IN FATUMNASI AREA, TIMOR TENGAH SELATAN (TTS) REGENCY, NUSA TENGGARA TIMUR PROVINCE - Kotta, Herry Zadrak (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
Cathodoluminescence (CL) is generated by visible light of minerals when they are bombarded with a beam of high energy electrons by a cathode gun. There are two types of chatodoluminescence, i.e., cold CL and hot CL. In the cold cathode microscopic equipment, the electrons are generated by an electric discharge between two electrodes under a low gas pressure, whereas in the hot CL microscope, the electrons are generated by heating a filament (2000-3000°C). This research to propose determine the growth of oolitic limestone’s cement by cathodoluminescence analysis and it’s implication to the engineering properties. Sectoral zoning and chevron-shape growth zoning exist in some coarse-grained calcite aggregates. The sectorial zoning of calcite as reflected by dull to bright CL color indicated as a water level fluctuation during cementation of the carbonate rocks, where the bright color of calcite indicating a shallower depth of water (oxidation) and dull to nonluminescence indicating a deeper level of the water (reduction). The results of this research, oolitic limestone (sample NS-1) showing sectorial zoning (chevron-shape) with at least 6 zonations, and have better engineering properties of other samples, according to SNI. 13-0089-87. Cathodoluminescence analysis is commonly used in the petroleum study, as evidenced in this research can be applied to determine the engineering properties of oolitic limestones in the study area.